Identification of 27 Novel Variants in Genes COL4A3, COL4A4, and COL4A5 in Lithuanian Families With Alport Syndrome - Cerkauskaite, Agne; Savige, Judy; Janonyte, Karolina; Jeremiciute, Ieva; Miglinas, Marius; Kazenaite, Edita; Laurinavicius, Arvydas; Strupaite-Sileikiene, Rasa; Vainutiene, Vija; Burnyte, Birute; Jankauskiene, Augustina; Rolfs, Arndt; et al. (Frontiers in Medicine, 2022)
Introduction: Alport syndrome (AS) is an inherited disorder characterized by hematuria, proteinuria, and kidney function impairment, and frequently associated with extrarenal manifestations. Pathogenic variants in COL4A5 usually cause X-linked Alport syndrome (XLAS), whereas those in the COL4A3 or COL4A4 genes are associated with autosomal dominant (AD) or recessive (AR) inheritance. To date, more than 3000 different disease-causing variants in COL4A5, COL4A3, and COL4A4 have been identified. The aim of this study was to evaluate the clinical and genetic spectrum of individuals with novel, pathogenic or likely pathogenic variants in the COL4A3-A5 genes in a previously unstudied cohort. Methods: In this study molecular analysis by Next Generation Sequencing (NGS) was performed on individuals from a Lithuanian cohort, with suspected AS. The presence of AS was assessed by reviewing clinical evidence of hematuria, proteinuria, chronic kidney disease (CKD), kidney failure (KF), a family history of AS or persistent hematuria, and specific histological lesions in the kidney biopsy such as thinning or lamellation of the glomerular basement membrane (GBM). Clinical, genetic, laboratory, and pathology data were reviewed. The novelty of the COL4A3-A5 variants was confirmed in the genetic variant databases (Centogene, Franklin, ClinVar, Varsome, InterVar). Only undescribed variants were included in this study. Results: Molecular testing of 171 suspected individuals led to the detection of 99 individuals with 44 disease causing variants including 27, previously undescribed changes, with the frequency of 9/27 (33,3%) in genes COL4A5, COL4A3 and COL4A4 equally. Three individuals were determined as having digenic AS causing variants: one in COL4A3 and COL4A4, two in COL4A4 and COL4A5. The most prevalent alterations in genes COL4A3-5 were missense variants (n=19), while splice site, frameshift, unknown variant and stop codon changes were detected more in genes COL4A4 and COL4A5 and accounted for 3, 3, 1 and 1 of all novel variants, respectively. Conclusion: Genotype-phenotype correlation analysis suggested that some variants demonstrated intra‐familial phenotypic variability. These novel variants represented more than half of all the variants found in a cohort of 171 individuals from 109 unrelated families who underwent testing. Our study expands the knowledge of the genetic and phenotypic spectrum for AS.